The implication of leaf anatomical structure for the selective breeding of lilacs - L. M. Pshennikova (Вавиловский журнал генетики и селекции, 2021)
The cultivars of the common lilac (Syringa vulgaris) grown in the south of the Russian Far East are not always winter-hardy and are often damaged by fungal diseases due to a very humid climate. A promising trend in the selective breeding of lilacs in Russia is the creation of new breeding material based on the gene pool of the broadleaf lilac (S. oblata) and its hybrids in order to introduce valuable adaptive traits into cultivars. The present work aimed to identify the traits of leaf anatomy in species and cultivars of Syringa resistant and susceptible to Pseudocercospora lilacis, the causative agent of brown leaf spot disease. The study was carried out on the living collection of the Botanical Garden-Institute, Far Eastern Branch, Russian Academy of Sciences (Vladivostok). The leaf anatomical structure of two Syringa species showing different degrees of resistance to P. lilacis in the monsoon climate of the Far East (resistant S. oblata and weakly resistant S. vulgaris, and also their hybrid cultivars) has been analyzed. The differences between species, subspecies, and cultivars are quantitative: they differ in the number of spongy mesophyll layers, the cell height in the first layer of palisade mesophyll, the cell height in the upper and lower epidermises, and the thickness of both mesophylls. The interspecific hybrids resistant or weakly resistant to P. lilacis (brown leaf spot disease) mainly retain the leaf anatomy structure of the maternal plant. One of the traits determining the resistance of hybrid lilac cultivars is an increased number of spongy mesophyll layers in the leaf blade. The study of leaf anatomy has shown that the four-layered spongy mesophyll leaf parenchyma correlates with the resistance of lilacs from the subsection Euvulgaris to P. lilacis. In S. oblata, this trait is inherited down the maternal line. To establish lilac cultivars resistant to fungal diseases, it is advisable to cross the two species (S. oblata and S. vulgaris) or their cultivars using one of S. oblata subspecies as a maternal plant.